Activation state and intracellular trafficking contribute to the repertoire of endogenous glycosphingolipids presented by CD1d [corrected]. - Muindi, K; Cernadas, M; Watts, G; Royle, L; Neville, D; Dwek, R; Besra, G; Rudd, P; Butters, T; Brenner, M (2010)
Myeloid antigen-presenting cells (APC) express CD1d molecules that present exogenous and endogenous lipid antigens that activate CD1d-restricted T cells, natural killer T (NKT) cells. NKT cell activation has been shown to mediate the potent downstream activation of other immune cells through cell-cell interactions and rapid, prolific cytokine production. Foreign antigens are not required for NKT cell activation. The endogenous lipids bound to CD1d are sufficient for activation of NKT cells in the setting of Toll-like receptor-induced cytokines. The most potent NKT cell antigens identified are glycosphingolipids (GSL). The GSL repertoire of endogenous ligands bound to CD1d molecules that are expressed in myeloid APC at steady state and in the setting of activation has not been delineated. This report identifies the range of GSL bound to soluble murine CD1d (mCD1d) molecules that sample the endoplasmic reticulum/secretory routes and cell surface-cleaved mCD1d that also samples the endocytic system. Specific GSL species are preferentially bound by mCD1d and do not solely reflect cellular GSL. GM1a and GD1a are prominent CD1d ligands for molecules following both the ER/secretory and lysosomal trafficking routes, whereas GM2 was eluted from soluble CD1d but not lysosomal trafficking CD1d. Further, after LPS activation, the quantities of soluble CD1d-bound GM3 and GM1a markedly increased. A unique alpha-galactose-terminating GSL was also found to be preferentially bound to mCD1d at steady state, and it increased with APC activation. Together, these studies identify the range of GSL presented by CD1d and how presentation varies based on CD1d intracellular trafficking and microbial activation.